Women’s NGOs in Pakistan - Jafar, A. author. aut Link
XI, 192 p.
Keywords: How do NGOs overcome the suspicion of them as "Western" agents? How do they convince people that contrary to common perceptions, they do not "lead women astray from Islam"? And how, in the context of poverty, religious fundamentalism, and ethnic conflict, do NGOs convince people that women s issues merit any attention at all? This book uncovers the skillful maneuvering that women s NGOs have to perform in order to survive in a hostile environment. Drawing on interviews, participant observation, and published materials by and about NGOs, this book analyzes the strategies used by Pakistani women s NGOs to advance women s rights in a conservative - and often antagonistic - environment.